Taxonomic revision of the genus Ponera Latreille, 1804 (Hymenoptera: Formicidae) of Taiwan and Japan, with a key to East Asian species - Leong, Chi-Man; Guénard, Benoit; Shiao, Shiuh-Feng; Lin, Chung-Chi (Zootaxa, 2019)
Ponera is a widespread genus of litter and soil ants. The highest diversity of the genus is found in Asia, with Taiwan and Japan being two of the most species-rich regions. Here, we systematically review the taxonomy of the 16 Taiwanese and Japanese Ponera species, two of which are new species from Taiwan: Ponera terayamai sp. n. and P. wui sp. n. A new key for Ponera species of East Asia is presented.